Inside the customer universe : how to build unique customer insight for profitable growth and market leadership - Andersen, Henrik, 1953-; Ritter, Thomas, 1970- (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2008)
Inside the Customer Universe reveals how an organization can become ahead of the game by focusing a its strategy on predicting customer needs rather than following them. This book provides a unique contribution to the field of customer management with a departure from current practice towards understanding customers as 'multi-individuals' and hence solving current confusions surrounding customer behaviour. Inside the Customer Universe's easy to implement tools, models and strategies provide the reader with the ability to create stable and sustainable customer understanding and, therefore, sust.
A quick guide to customer universe based execution -- The executive challenge of driving EBITDA growth -- The challenges of current segmentation models -- Identifying customer types : inside the customer mind -- Identifying roles and scenes : inside situations and occasions -- CUBEical segmentation : the platform for achieving market leadership -- CUBEical strategy : where and how to compete -- CUBEical implementation : how to take the lead -- CUBEical thinking : how it links to other business frameworks -- The fast moving consumer goods universe -- The key account management universe -- The mergers and acquisition universe.
Includes index.
Print version record.
John Wiley and Sons
Keywords: Customer relations; Marketing; Marketing; marketing; BUSINESS & ECONOMICS -- Marketing -- Research; Customer relations; Marketing